Clinical Strategies for the Chemoprevention of Localized Prostate Cancer - Nagi B Kumar (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Prostate cancer is a complex, heterogeneous disease that demands concurrent inhibition of multiple hallmark-associated pathways. Prostate cancer is the most common cancer among men in the United States and the second leading cause of cancer-related deaths. Metastatic castration-resistant prostate cancer is still a fatal disease. On the other hand, between 2016 and 2020, about 70% of Prostate cancer cases were diagnosed at a localized stage. Evolving data demonstrate that men with low-grade cancers treated with definitive therapies may now be exposed to morbidities of overtreatment and poor quality of life, with little or no benefit in terms of cancer-specific mortality. Active surveillance is thus the recommended management strategy for men with low-grade disease. Although this subgroup of men has reported anxiety during the AS period, they account to be highly motivated to make positive lifestyle changes to further reduce their risk of prostate cancer progression, underscoring the urgent need to identify novel strategies for preventing progression of localized prostate cancer to metastatic disease through pharmacologic means, an approach termed chemoprevention. Over the past decade, there have been several attempts to identify and evaluate agents and approaches for Prostate cancer chemoprevention targeting healthy men or men at relatively higher risk for Prostate cancer (HGPIN) or early phase trials of short duration in Prostate cancer patients with localized disease during the 4-6 week pre-surgical window (Biopsy to prostatectomy). Several promising agents such as soy isoflavones, lycopene, Selenium, Vitamin E, resveratrol, green tea catechins, and other nutritional approaches have been examined over the past 2 decades. However, currently, there are several limitations in the research approach used to systematically examine these agents and approaches for chemoprevention. Consequently, there are no concrete recommendations that can be provided to men who are on active surveillance to reduce the risk of progression from early to advanced stage of prostate cancer. The goal of this review is to summarize the current agents and approaches evaluated, targeting men on active surveillance, recognize the gaps, and identify a contemporary and comprehensive path forward. Results of these studies may inform the development of well-powered phase III clinical trials and ultimately provide a strategy for clinical chemoprevention in men on active surveillance, for whom, currently, there are no options for reducing the risk of progression to metastatic disease. Early phase trials must include objective markers of compliance with to study agent throughout the trial, in addition to pill counts and self-reported daily study-agent intake logs.